Presidential Dignity and Democratic Paradox in Indonesia's 2023 Criminal Code: A Critical Paradigm Approach - Solehuddin; Pujiyono; Irma Cahyaningtyas; Fines Fatimah (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2026)
This research is motivated by the urgency to critically evaluate the reintroduction of offenses against the President's dignity in Article 218 of Law Number 1 of 2023 (the New Indonesian Criminal Code). While intended to protect state symbols, this regulation controversially mirrors colonial-era laws and fails to fully accommodate the democratic and socio-cultural values of modern Indonesian society. Unlike previous studies that predominantly focus on the normative bounds of free speech, this study offers a novel approach by utilizing the Critical Theory paradigm to deconstruct the power dynamics, colonial legacy, and discriminatory nature embedded within the law. Employing a normative legal research method with statutory and conceptual approaches, this study reveals that Article 218 paragraph (1) remains obscure and discriminatory, failing to reflect the